Analysis of 100 consecutively visiting uterine cervical cancer patients in cancer hospital - Shrestha, Binuma; Subedi, Hem Nath; Paudel, Sachinda; Pandey, Manju; Acharya, Bijay Chandra; Gurung, Sarita (Nepalese Journal of Cancer, 2021)
Background: Cervical cancer is the most common cancers in female population of Nepal. Though considered a slow growing cancer, majority of patients still present very late. Methodology: One hundred patients of cancer cervix were retrospectively analysed to see their spectrum of clinical presentation and care pathway from January 2012 to April 2012. Results: The clinical spectrum showed they presented to clinic after average of 9 months of symptoms. Squamous cell cancers were the main histology. Majority of cases were in FIGO stage of II and IIIB. Radiation therapy with tele-therapy and brachytherapy was the main modality of treatment (94%) of cases. Conclusion: Late stage of presentation is a very common phenomenon in the patients with cancer of cervix. Need screening programs in systematic manner to detect early stage diseases and for better care.